On the estimation of the remainder term in the multidimensional central limit theorem - Jasiūnas, H. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Г. Ясюнас. Об оценке остаточного члена в многомерной центральной предельной теоремеH. Jasiūnas. Liekamoje nario įvertinimas daugiamatėje centrinėje ribinėje teoremoje